Compliance Risk Management (CRM) from the Perception of Users - Levana Virginia Winahyu; Siti Nuryanah (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2024)
Compliance Risk Management (CRM) continues to be developed through DJP Director Circular Letter No. SE-39/PJ/2021 by implementing the Big Data Analytics (BDA) concept. This study aims to evaluate the effectiveness of using the CRM information system at KPP Pratama Jakarta Palmerah based on user perceptions through the Technology Acceptance Model (TAM). This study combines elements of quantitative and qualitative methods with concurrent triangulation. The data used includes primary data in questionnaires and interviews with users, Account Representative and Tax Auditor. This study concluded that CRM information system meets the elements of perceived usefulness and perceived ease of use. However, users still face various obstacles while operating CRM. The results of this study also propose several suggestions from users for improving and developing CRM in the future. In addition, this study is expected to be a reference for DJP in developing CRM analysis tools.